Legal Analysis of the Misuse of Live Streaming on the TikTok Platform as a Medium for Promoting Online Gambling - Rentina Hutasoit; Aris Toteles; Claudia Yuni Pramita (Green Publisher Indonesia, 2026)
The rapid development of information and communication technology has significantly changed human behavior, particularly in the realm of social media, with platforms like TikTok gaining massive popularity. While TikTok’s live-streaming feature provides opportunities for content creators to engage with their audiences and promote products, it has also led to the misuse of this platform for illegal activities, such as the promotion of online gambling. This research aims to conduct a juridical analysis of how TikTok’s live-streaming feature has been exploited to promote online gambling, using a case study involving a popular TikTok live streamer. The study evaluates the legal frameworks regulating the promotion of online gambling through social media, focusing on the Indonesian ITE Law and the Criminal Code. A normative juridical approach is employed to assess violations of legal provisions by influencers, specifically their actions in promoting gambling sites under the guise of entertainment. The results reveal that while TikTok’s live-streaming feature can be used for legitimate purposes, it can also facilitate illegal gambling promotion. The study concludes by recommending improved legal enforcement and policy development to address these challenges effectively.